Mapping collaborative: co-authorship network analysis in the Journal of Graph Theory (2001-2015) - Roslan Hasni; Nur Laila Ilyana Mohamad Nuruldin; Sumarni Abu Bakar; Sharifah Kartini Said Husain; Gobithaasan Rudrusamy; Zurita Ismail (Penerbit Universiti Kebangsaan Malaysia, 2025)
The co-authorship of articles in peer-reviewed journals contributes to knowledge based on the research community. Co-authorship can be termed as a collaboration between two or more authors if they publish a scientific work together. The main goal of this study is to analyse the co-authorship network of scientists who published their articles in the Journal of Graph Theory. The co-authorship data of 810 articles published in the journal from 2001 until 2015 was collected. We used the principle of network sciences in which the network nodes represent authors who are connected with the edges if they co-authored papers. The analysis was conducted using the network science indicators and visualisations of the co-authorship network and thereafter centrality measures such as degree centrality, betweenness centrality, and closeness centrality are used to identify the authors’ connectedness and influence in the network. The study identifies key influential authors based on centrality measures, demonstrating their pivotal roles in the network. Furthermore, the prevalence of multi-author collaborations underscores the collaborative nature of research in this domain.